O ajuizamento estético da obra de arte: uma configuração da recepção crítica a partir de Danto e Benjamin - Rízzia Soares Rocha (2017)
Contemporary artistic production has brought changes to the concept of art that made traditional values ineffective. This thesis proposes a reconfiguration of artwork reception based on Walter Benjamin and Arthur Dantos works. This reconfiguration does not rely on aesthetic regulations and thus challenges the common contemplative attitude of the traditional spectator. This receptive mode, which resulted from the ascension of the bourgeoisie, should be replaced with an active observer whose receptive work makes up the artwork. Therefore, the artistic object is considered to be a project or unfinished work that completes itself through reception, which is based on critical reflection. This scenario demands modifications of the concept of criticism and the relationship between the critic and the contemporary artistic production. Benjamin and Danto set the guidelines for the critical reception reconfiguration that caters for the particularities of the contemporary artistic phenomenon and allows the artwork to convey meanings to life. With the dissolution of a priori parameters for the artwork evaluation and the feeling that the artistic phenomenon has reduced itself to arbitrary attributions of artwork status, the new criticism concept prevents the meaning of art from being converted into a tool to maintain the status quo or restricted to a group of experts.